Models/theories of development and the concept of social development - Guzman, Alfonzo Z. (Philippine Journal of Public Administration, 1993)
Various models/theories have emerged through the years in response to the need to gain a better understanding of the problems of development and underdevelopment in the Third World. These include, under the orthodox paradigm: the classical model, the neoclassical model, the expanding capitalist nucleus model, the structuralist model, the Maoist model, and the basic needs model. The radical/political economy paradigm includes: the Marxist model, the neo-Marxist model and the- dependency model. Each of the model has social development dimensions. A review of these dimensions led to a conclusion that a viable development in the Philippines requires fundamental extrication of its economy from the orbit of the world capitalist system and the pursuit of an independent economic policy.